Mental healthcare for young and adolescent LGBTQ+ individuals in the Indian subcontinent - Gaur, Prithvi Sanjeevkumar; Saha, Sreoshy; Goel, Ashish; Ovseiko, Pavel; Aggarwal, Shelley; Agarwal, Vikas; Haq, Atiq Ul; Danda, Debashish; Hartle, Andrew; Sandhu, Nimrat Kaur; Gupta, Latika (Frontiers in Psychology, 2023)
The coronavirus disease (COVID-19) pandemic has led to a significant change in the way healthcare is dispensed. During the pandemic, healthcare inequities were experienced by various sections of society, based on gender, ethnicity, and socioeconomic status. The LGBTQ individuals were also affected by this inequity. There is a lack of information on this topic especially in the developing countries. Hence this issue requires further exploration and understanding. Previous literature briefly explored the mental, physical, and emotional turmoil faced by the LGBTQ community on a regular basis. They feared rejection by family and friends, bullying, physical assault, and religious biases. These issues prevented them from publicly speaking about their sexual orientation thereby making it difficult to collect reliable data. Although they require medical and psychological treatment, they are afraid to ask for help and access healthcare and mental health services. Being mindful of these difficulties, this article explores the various underlying causes of the mental health problems faced by LGBTQ individuals, especially, in the Indian subcontinent. The article also examines the status of healthcare services available to Indian sexual minorities and provides recommendations about possible remedial measures to ensure the well-being of LGBTQ individuals.